Հայ Առաքելական Սուրբ Եկեղեցու տաղավար տոների քրիստոսաբանական և փրկագործական խորհրդաբանութեան շուրջ - Աբրահամյան, Հասմիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Рождество Христово, Воскресение Христово, Успение Пресвятой Богородицы и Распятие были включены в первый письменный церковный календарь в начале V века. Праздник Преображения Господня в Календаре появился не позже, чем в VII веке. Однако, праздники были определены как главные го- раздо позже. В XI—XII вв. отцы Армянской Церкви объявили Рождество, Воскресение и Преображение Господня главными праздниками или Навакатиком – праздником обновления и спасения. А в начале XIV века добавились еще и праздники Успения Пресвятой Богородицы и Воздвижения Креста Господня. Главная цель установления великих праздников — избежать влияний Халки- донских ритуалов и догматики. Эти праздники символизируют Христологи- ческую позицию Армянской Церкви и ее учение о Спасении. В связи с этим Армянская Церковь установила их главными праздниками. The feasts of Holy Nativity and Epiphany of Christ, the Resurrection of Christ, the Assumption of the Mother of God and the Crucifixion of Jesus were included in the first liturgical calendar of the Armenian Apostolic Church at the beginning of the 5th century. The feast of Vardavar or Transfiguration was included in the calendar no later than at the beginning of the 7th century. However, they were identified as great feasts much later. In the 11th—12th centuries, the Armenian Church Fathers declared the Nativity and Epiphany, the Resurrection of Christ and Transfiguration as great feasts or Navakatik — feast of renewal and salvation. At the beginning of the 14th century, the feasts of the Assumption of the Mother of God and the Exaltation of the Holy Cross were also added to the great feasts. The main purpose of establishing the great feasts is to protect the Armenian Church from Chalcedonian rituals and dogmas, because these feasts symbolize the Christological position and the doctrine of salvation of the Armenian Church. For this reason, the Armenian Church set them up as great feasts.
Keywords: Կրօնագիտութիւն; Հայոց եկեղեցի; Եկեղեցական տոներ